Etiological characterization of acute undifferentiated febrile illness in Apartadó and Villeta municipalities, Colombia, during COVID-19 pandemic (2023)
ABSTRACT: Background: Acute undifferentiated febrile illness (AUFI) is one of the leading causes of illness in tropical regions. Although malaria is the most important cause, other pathogens such as Dengue (DENV), Leptospira and recently, Coronavirus Disease 2019 (COVID-19) have gained importance. In Colombia, few studies aimed to identify the etiology of AUFI. Most of them performed in Apartadó and Villeta municipalities, identifying the active circulation of several pathogens. Thus, we conducted a cross-sectional study in these municipalities to characterize the etiologies of AUFI during COVID-19 pandemic. Methods: An active surveillance was conducted between September and December 2021 in local hospitals of Apartadó and Villeta municipalities. Febrile patients were enrolled after voluntarily agreeing to participate in the study. Ten different etiologies were evaluated through direct, serological, molecular and rapid diagnostic methods. Results: In Apartadó a confirmed etiology was found in 60% of subjects, DENV (25%) being the most frequent, followed by leptospirosis (16.7%), malaria (10%), COVID-19 (8.3%), spotted fever group (SFG) rickettsiosis (6.7%) and Chikungunya (1.7%). In Villeta, a specific etiology was confirmed in 55.4% of patients, of which SFG rickettsiosis (39.3%) was the most frequent, followed by leptospirosis (21.4%), DENV (3.6%) and malaria (1.8%). No cases due to Mayaro, Yellow Fever, Oropouche and Venezuelan Equine Encephalitis viruses were detected. Conclusion: We confirm the relevance of dengue fever, leptospirosis, SFG rickettsiosis, COVID-19 and malaria as causes of AUFI in the municipality of Apartadó, and highlight the great importance of SFG rickettsiosis as the main cause of AUFI in the municipality of Villeta. Keywords: Arbovirus; COVID-19; Leptospira; Malaria; Rickettsia.